Memahami idealisme manusia pada masa dewasa dan masa lansia dari sudut pandang psikologi perkembangan - Rosidi, Atsilah Nabigh; Laksana, Dicky Wahyu Tri; Shabira, Mikyatush (Maliki Interdisciplinary Journal, 2026)
Idealism is a psychological concept that reflects the values, beliefs, and goals that a person considers crucial in living their life. In the context of developmental psychology, idealism is not fixed; it will change with age. This study seeks to identify the forms and changes in idealism in adulthood and old age by referring to developmental theories that individuals in adulthood tend to direct their idealism towards career achievement, quality interpersonal relationships, contributions to society, and the achievement of meaning in life. Conversely, in old age, idealism shifts to a focus on the wisdom of reflection on life experiences, the continuation of personal values, and the desire to achieve self-integrity. These changes are influenced by various biological, social, and psychological factors, including life experiences, changes in social roles, and cognitive processes such as a decrease or increase in the ability to control emotions. This study shows that idealism in both phases of life plays a vital role in psychological well-being, self-understanding, and the meaning of life. By understanding these changes, this study contributes to enriching the field of developmental psychology regarding motivation, values, and human adjustment throughout life.